Strengthening religious moderation awareness among post-conflict students’ through interactive Indonesian language learning - Tabrani, Akhmad; Viono, Tono (KEMBARA: Jurnal Keilmuan Bahasa, Sastra, dan Pengajarannya, 2024)
Information and communication technology plays an important role in realizing a society towards sustainable knowledge, but it can also trigger radicalization in socio-cultural life. One of the interventions to learning is done by instilling the value of religious moderation. This research aims to develop interactive gamification multimedia that integrates the concept of religious moderation that will be implemented in learning discussion texts in Indonesian language subjects. The research method was adapted from the Borg and Gall development research model, which consists of four stages, namely 1.) pre-field test to get validation from experts and fellow practitioners, 2.) main product revision, 3.) main product revision, 3.) main product revision, 3.) main product revision. Main product revision, 3.) field test to add information related to learning outcomes and awareness of religious moderation, and 4.) operational product revision. This research has successfully developed a gamified interactive multimedia product with an average expert validation result of 3 or in the high category. The attitude of religious moderation after being tested has largely shown an understanding and attitude towards moderation. Student learning outcomes in discussion text material increased significantly as evidenced by pre-experiment results of <0.005. However, this development research was only limited to a small scope of Indonesian language subject matter. This research provided a new direction in the development of teaching materials, especially interactive multimedia on language learning field. The interactivity and gamification side of the learning media could be further developed to make the game aspect more challenging, realistic, and related to students' daily lives.